Effect of AlN powders on the debinding and sintering behavior, and thermal conductivity of injection molded AlN ceramics. Issue 18 (15th December 2019) - Lu, Huifeng; Qin, Mingli; Wu, Haoyang; He, Qing; Liu, Chang; Mu, Xiaodong; Wang, Yuelong; Jia, Baorui; Qu, Xuanhui
Abstract: This work focuses on fabricating aluminum nitride (AlN) parts by powder injection molding (PIM), the influences of using two kinds of AlN powder as raw materials, and the effects of various AlN powders on injection molding, debinding, sintering and the thermal conductivity of solid parts. Two kinds of AlN powders, carbonthermally reduced powders (C-R) and directly nitrided powders (D-N), have been chosen as the raw materials. After the powder injection molding (PIM) process, C-R green parts (with white color) and D-N green parts (with grey color) were prepared. The C-R sample has higher sintering activity than that of the D-N sample, and it can achieve nearly 100% relative density at 1850 °C while the densification of the D-N sample was realized at 1900 °C. Due to the small particle size, high specific surface area, near spherical shape and high purity of C-R powder, the C-R sintered sample possesses a higher thermal conductivity (183W·m −1 ·k −1 ) than that of the D-N sintered sample (130 W m −1  k −1 ).